1974
DOI: 10.1128/am.28.5.892-894.1974
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Diketopiperazines by Penicillium italicum Isolated from Oranges

Abstract: Prolyl-2-(1′,1′-dimethylallyl)tryptophyldiketopiperazine and 12,13-dehydroprolyl-2-(1′,1′-dimethylallyl)tryptophyldiketopiperazine, known metabolites of Aspergillus ustus , were produced in low yield by Penicillium italicum in liquid culture and on unsterilized orange peel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…81 The infected area typically displays blue or bluish-green sporulation, surrounded by a small band of unsporulated white mycelium and a broad band of soft, watersoaked peel. 65 Some studies have reported metabolites produced in the in vitro cultures of P. italicum, such as deoxybrevianamide E; [82][83][84] dehydrodeoxybrevianamide E; 83 xanthocyllin X; 84 formylxanthocillin X; 84 arabenoic acid, 84 and dehydrofulvic acid, 5-hydroxymethylfuric acid. 84 Despite these findings, the specific role of these metabolites in the interaction between P. italicum and its citrus host remains unclear.…”
Section: Green Mold Disease (Penicillium Digitatum)mentioning
confidence: 99%
“…81 The infected area typically displays blue or bluish-green sporulation, surrounded by a small band of unsporulated white mycelium and a broad band of soft, watersoaked peel. 65 Some studies have reported metabolites produced in the in vitro cultures of P. italicum, such as deoxybrevianamide E; [82][83][84] dehydrodeoxybrevianamide E; 83 xanthocyllin X; 84 formylxanthocillin X; 84 arabenoic acid, 84 and dehydrofulvic acid, 5-hydroxymethylfuric acid. 84 Despite these findings, the specific role of these metabolites in the interaction between P. italicum and its citrus host remains unclear.…”
Section: Green Mold Disease (Penicillium Digitatum)mentioning
confidence: 99%
“…30 Our new biosynthetic hypothesis for (+)-brevianamide A (1) involves an alternative biosynthetic precursor, (+)-dehydrodeoxybrevianamide E (9), which is a known natural product isolated from various Penicillium and Aspergillus species (Figure 2, Pathway 3). [32][33][34] Crucially, the diketopiperazine ring in (+)-dehydrodeoxybrevianamide E ( 9) is already at the oxidation level required for a later Diels-Alder reaction. Our pathway involves a point-topoint chirality transfer via a sequential diastereoselective indole oxidation, stereospecific…”
mentioning
confidence: 99%